Assessorias Departamentais - Piedade, André Matos; Toquetão, Cleide Lemes da Silva; Caciatore, Magda Requena; Oliveira, Maria Bertolina Mesquita de; Moura, Peterson; Lima, Miriam Regina Mouro Ferraz (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Peterson Moura